1997
DOI: 10.1002/(sici)1098-2396(199709)27:1<1::aid-syn1>3.0.co;2-9
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation ofd-amphetamine effects on the binding of dopamine D-2 receptor radioligand,18F-fallypride in nonhuman primates using positron emission tomography

Abstract: We have investigated the ability of dopamine to compete with the binding of the high affinity dopamine D2 receptor positron emission tomography (PET) radioligand, 18F-fallypride. In vitro dissociation of 18F-fallypride with dopamine in rat striatal homogenates exhibited a dissociation rate, k(off), of 1.76 x 10(-2) min(-1) while the association rate constant, k(on), was found to be 5.30 x 10(8) M(-1) min(-1). This resulted in a dissociation constant, K(D) of 33 pM for 18F-fallypride. For in vivo studies, we in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…The D2/3 receptors were the first to be imaged using [ 11 C]- N -methylspiperone in the living human brain using PET (Wagner et al, 1983). Since then a number of new radioligands to measure these receptors have been developed, e.g., [ 18 F]-FESP, [ 11 C]-raclopride, [ 11 C]- N -methylbenperidol, [ 11 C]-FLB 457, [ 18 F]-fallypride (Ehrin et al, 1985; Coenen et al, 1987; Suehiro et al, 1990; Halldin et al, 1995; Mukherjee et al, 1997). Since PET imaging measures the binding of a radioligand to a receptor, changes in binding over time can be attributed to up-regulation or down-regulation of the receptor.…”
Section: Introductionmentioning
confidence: 99%
“…The D2/3 receptors were the first to be imaged using [ 11 C]- N -methylspiperone in the living human brain using PET (Wagner et al, 1983). Since then a number of new radioligands to measure these receptors have been developed, e.g., [ 18 F]-FESP, [ 11 C]-raclopride, [ 11 C]- N -methylbenperidol, [ 11 C]-FLB 457, [ 18 F]-fallypride (Ehrin et al, 1985; Coenen et al, 1987; Suehiro et al, 1990; Halldin et al, 1995; Mukherjee et al, 1997). Since PET imaging measures the binding of a radioligand to a receptor, changes in binding over time can be attributed to up-regulation or down-regulation of the receptor.…”
Section: Introductionmentioning
confidence: 99%
“…Each anesthetized animal was positioned in the ECAT 933 PET scanner with horizontal imaging slices parallel to the orbital-meatus (OM) plane. The tracer used to assess DA D 2 receptors was [ 18 F]-Fallypride ([ 18 F]FAL), an F-18-labeled raclopride analog developed by Mukherjee et al (1997). [ 18 F]FAL was prepared using a procedure adopted from Mukherjee et al (1995).…”
Section: Methodsmentioning
confidence: 99%
“…Rh5-HTTLPR genotype ( l/l vs. l/s and s/s ) were determined. We also measured striatal DA D 2 R function in positron emission tomography (PET) scans using [ 18 F]-fallypride ([ 18 F]FAL) developed by Mukherjee et al (1997). [ 18 F]FAL is currently the PET tracer of choice for DA D 2 receptor studies because of its optimal imaging properties (Kessler et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Development of high-affinity radioligands for the D 2/3 receptor such as [ 18 F]Fallypride have enabled noninvasive assessment of extrastriatal D 2/3 receptor densities during pharmacologic (Slifstein et al, 2010) and behavioral paradigms (Albrecht et al, 2014). For example, PET experiments with [ 18 F]Fallypride in monkeys showed that amphetamine challenge may induce a striking reduction in binding in the anterior cingulate cortex (ACC) (Mukherjee et al, 1997). It has also been shown that a single [ 18 F]Fallypride scan protocol and linearized simplified reference region modeling (LSSRM) analysis can be used to measure extrastriatal dopamine release induced by a behavioural task (Christian et al, 2006;Lataster et al, 2011).…”
Section: Introductionmentioning
confidence: 99%